KSENIJA VIDMAR HORVAT: ZAMIŠLJENA MATI: SPOL IN NACIONALIZEM V KULTURI 20. STOLETJA: Ljubljana: Znanstvena založba Filozofske fakultete, 2013 (Zbirka Razprave FF). - Vollmaier Lubej, Janja (Slavia Centralis, 2020)
The article presents a monograph by Ksenija Vidmar Horvat Zamišljena mati, which deals with the image of mother and motherhood in the 20th century.
Keywords: review; Ksenija Vidmar Horvat; Zamišljena mati; mother; motherhood; cultural history